FAKTOR FAKTOR YANG MEMPENGARUHI UNMET NEED KB PADA WANITA USIA SUBUR DI WILAYAH BUNGUS PADANG, SUMATERA BARAT - Yolanda Dwi Santi Violentina; Husna Yetti; Arni Amir (-, 2023)
ABSTRACTUnmet needs for family planning is a problem in family planning (KB) that needs special attention. The highest unmet need for family planning in Padang City is in Bungus District, with a percentage of 29.6%, while the national target is 6.5%. The purpose of this study was to analyze the factors that influence the unmet need for family planning in the Bungus Padang area. This study uses a qualitative descriptive research method which was carried out in March-May 2019 at the Bungus Health Center, Bungus BKKBN Representative Office, and the Bungus Health Center working area with samples taken using the principles of appropriateness and adequacy, namely the Head of the MCH/KB Responsible Division, PLKB, two midwifes, and five women of childbearing age. The results of the analysis show that there are obstacles that cause the high unmet need for family planning, namely the lack of human resources, lack of socialization, lack of the role of midwives, religious factors, and the husband's support. The conclusion is that the unmet need for family planning in the Bungus area is still high due to various factors. The process of socialization and implementation needs improvement in order to increase community activity. Keywords: Husband’s support, Role of Midwife, Unmet need for family planningABSTRAKUnmet need KB merupakan permasalahan yang terdapat pada keluarga berencana (KB) yang perlu mendapatkan perhatian yang khusus. Angka unmeet need KB tertinggi di Kota Padang terdapat di Kecamatan Bungus dengan persentase 29,6%, sedangkan target nasional 6,5%. Tujuan penelitian ini untuk menganalisis faktor yang mempengaruhi unmet need KB di wilayah Bungus Padang. Penelitian ini menggunakan metode penelitian deskriptif kualitatif yang dilaksanakan pada bulan Maret-Mei 2019 di Puskesmas Bungus, Kantor Perwakilan BKKBN Bungus dan wilayah kerja Puskesmas Bungus dengan subjek penelitian diambil menggunakan prinsip appropriateness and adequacy yaitu pada Kepala Bidang Penanggung jawab KIA/KB, PLKB, dua orang bidan pustu, 5 orang wanita usia subur. Hasil analisis menunjukkan bahwa terdapat kendala yang menyebabkan tingginya unmet need KB adalah kurangnya Sumber Daya Manusia (SDM), kurangnya sosialisasi, kurangnya peran bidan, faktor agama dan dukungan suami. Masih tingginya unmet need KB di Daerah Bungus yang disebabkan oleh berbagai faktor. Proses sosialisasi dan pelaksanaan membutuhkan perbaikan agar dapat meningkatkan keaktifan masyarakat.Kata Kunci : Dukungan Suami, Peran bidan, Unmet need KB